An Analysis Reading Difficulties of Narrative Text in Online Learning at the Tenth Grade Students of SMKN 4 Jambi in Academic Years 2019/2020 - Dini Dini; Suyadi Suyadi; Kartika Dewi (Universitas Batanghari Jambi, 2021)
Reading is the process of receiving interpreting information in language from via the medium of print. The purpose of this research is to analysis reading difficulties of narrative text in online learning by using Edmodo. The objective of this research is to identify the students’ difficulties. The research conducted at SMK N 4 Jambi in academic years 2019/2020. The population of this research is tenth grade students of fashion class II. Type of the research is qualitative the data were obtained by using online interview. Overall, the result of this research is most of the students have difficulties in understanding narrative text by using Edmodo application which the students argued that the explanation of the generic structure, language feature, finding main idea of the narrative text and students’ vocabularies are limited. But the difficulties could be solved by Edmodo communication tools which the teacher and all students could make the discussion about their difficulties, especially in learning reading narrative text.Keywords: Reading difficulties, Narrative text, Online Learning.